2018
DOI: 10.7150/jca.24782
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Immunotherapy with or without Cisplatin for metastatic lung cancer non-small cell lung cancer disease: In vivo Study. A more efficient combination

Abstract: Lung cancer is the leading cause of cancer death after prostate cancer for males and breast cancer for females. There are novel therapies in the past five years such as; tyrosine kinase inhibitors and most recently in the last two years immunotherapy. Immunotherapy is currently being investigated if it can be administered alone or in combination. Previously we have investigated whether immunotherapy compounds can be produced as aerosols, and in the current study we investigated the safety and efficiency indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Again abscess formation has been observed in a previous case series due to high PD-L1 expression and it is common in large NSCLC lesions [161]. There are two more studies that support that local aerosol administration of immunotherapy has a favorable effect and could be used alternatively in NSCLC for selected patients [162,163].…”
Section: Immunotherapymentioning
confidence: 70%
“…Again abscess formation has been observed in a previous case series due to high PD-L1 expression and it is common in large NSCLC lesions [161]. There are two more studies that support that local aerosol administration of immunotherapy has a favorable effect and could be used alternatively in NSCLC for selected patients [162,163].…”
Section: Immunotherapymentioning
confidence: 70%
“…In another study, a combination of CIS and nivolumab was used for nebulized inhalation therapy. The results showed that administering immunotherapy before CIS treatment extended the survival of mice and reduced lung metastasis ( 128 ). However, it is noteworthy that the model used in that study involved subcutaneous tumor implantation in the foot, and further observation is needed to evaluate the direct therapeutic effect on in situ lung cancer.…”
Section: Preclinical Application Of Micron/nddsmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) remains the leading cause of mortality from cancer, and surgery combined with chemotherapy has increased the long-term survival rate of patients with NSCLC (1). Chemotherapy is effective by triggering the death of tumor cells, but the occurrence of drug resistance can limit its efficacy (2).…”
Section: Introductionmentioning
confidence: 99%